Tindak Tutur Ilokusi Ekspresif dan Direktif dalam Komik “Witch Hunt” Berbasis Webtoon Karya Sso Park ( Kajian Pragmatik) - Rizky Ananda Putri; Hanafi Hanafi (Journal on Education, 2024)
This research has the main purpose to classify and explain the various forms of illocutionary speech acts, both expressive and directive, contained in the comic entitled "Witch Hunt" by Sso Park. The research method applied is descriptive qualitative research. The data source used in this research is the speech uttered by the characters in the comic, which can be accessed through the Line Webtoon application. In an effort to understand conversations in comic narratives, this research uses the pragmatic analysis method. Pragmatic analysis is the study of language use in communication, with a special focus on the relationship between the sentence and the context and situation to which the sentence refers. Speech acts in the context of pragmatic studies are divided into three main categories, namely locution, illocution, and perlocution. The data collection method used in this research is the documentation method, by applying reading and note-taking techniques to obtain the necessary information. Through in-depth analysis, the researcher managed to identify 89 forms of illocutionary speech acts in the comic "Witch Hunt" by Sso Park. Of these, there are 51 expressive illocutionary speech acts and 38 directive illocutionary speech acts.